As teias que movem a formação continuada de docentes do ensino superior e suas práticas inclusivas : entrelaces entre Brasil e México - Coutinho, Rosalba Lima (2018)
The theme of this study is the continued training of higher education teachers from the Special Education perspective. The investigative search focused on two processes of continued training addressed to teachers who are in higher education classes. The organization of the first one entitled “Strategies of Teaching and Learning for the Visually Impaired” took place in three modules and aimed to assist the teachers from Universidad Veracruzana, Xalapa Campus, State of Veracruz, Mexico. The State University of Espírito Santo (UFES) performed the second formative process which aimed to provide students with a critical reflection on the educational matters in higher education, as well as subsidize their didactic and pedagogical formation for this level of teaching. This research was qualitative, outlined in the scope of international comparative studies. A data collecting was employed supported by institutional documents, through questionnaires, semistructured interviews involving a group of Brazilian and Mexican teachers who participated in the courses which we have investigated about. Our reflections and discussions have as reference the conjectures of Figurational or Procedural Sociology, from Norbert Elias, specially focusing on figuration and interdependence concepts (ELIAS, 1994; 2001) in dialogue with the literature which deals with continued training for teachers. We could observe that the teachers sought new ways, in the continued training, to face the difficulties that they judged to be also recurrent in the work of other teachers into the same institution. From the participants’ perspective, the continued training has contributed in professional and personal trajectories for those who want to qualify their work. The majority of participants emphasized advances in their teaching work after the course. For them, the continued training gave a boost for a review in the educational process, making them look for unusual teaching mechanism/ strategies. These aspects lead to emphasize the importance of recognizing the teachers’ formation as a necessary space for reflection on the improvement of the objective and subjective conditions for teaching work performance. It was possible to note that the experiences of formation carried out into the two universities make mandatory for them to establish dialogue with other teaching levels, instigating new debates and political proposals which more effectively motivate the disabled students to continue studying. This formative experience with teachers also collaborates with the breaking of the historical formulation which asserts that the pursuit of school knowledge is exclusively a family’s responsibility or of the disabled person on its own. Finally, based on the data collected in this study, the university, via an institutional policy which assures common spaces for dialogue and teachers’ formation, will be able to contribute with the validation of movements which give new meanings for the teaching concepts and practices, assuring, this way, a social high quality education for all.